Activation of Strong Bonds Enabled by Arene π-Coordination - Mutoh, Yuichiro; Ilies, Laurean (Synthesis, 2025)
π-Coordination of an arene to a metal fragment decreases its electron density and has been often utilized to accelerate nucleophilic aromatic substitution, for example. By contrast, this strategy has only recently been applied to transition metal–catalyzed C–H bond functionalization. This short review summarizes the development of the field, with the hope to further stimulate interest in this methodology. Transition metal–catalyzed and –mediated C–H activation of arenes η6-coordinated to chromium and other metals is mainly discussed; to highlight the potential of this strategy for organic synthesis, the activation of other strong bonds, with a focus on C–O bond activation, is also presented.
Keywords: π-Coordination; η6-Complex; Arene functionalization; C–H bond activation; C–O bond activation; C–Halogen bond activation